Sesame Production Characteristics and Challenges in Western Kenya - Koitilio, B.; Chepkoech, E.; Kinyua, M.; Kiplagat, O. (African Journal of Education,Science and Technology (AJEST), 2022)
Sesame is one of the most important oilseed crops in the tropical and subtropical regions of the world. Despite its importance, sesame yield potential in Kenya is very low. The objective of this study was to identify constraints limiting sesame production in Western Kenya. A survey was undertaken in Busia, Bungoma and Siaya Counties of Western Kenya involving a representative sample of 153 sesame farmers. To identify the sampling units, a three-phase stratified sampling was used to select the three counties out of the 10 counties in western Kenya, followed by selection of smaller sampling units from the selected counties. Subsequently, snowball sampling was used to identify the 153 respondent sesame farmers in the selected sampling units. The sampled farmers were then interviewed using a structured questionnaire. The data obtained was analysed using Statistical Package for Social Scientists (SPSS) version 20. The findings showed that majority of sesame farmers were aged above 41years at 66%. Among the respondents, 39% were male while 61% were female. Adult females at 56% mainly provided sesame farming labour. On land tenure, 62% of the respondents inherited land from their parents. The largest proportion (67%) of the respondents obtained seed from the grain markets whereas a majority of the respondents (80%) planted sesame as a mono-crop, in rows (69%) and did not use any fertilizer (81%) in producing their crop. Farmers did not grow any improved sesame cultivars with three popular genotypes being grown that included Local white, Sudan cultivar (advanced) and Local Brown. Pests and diseases were a minor problem in sesame production in the study area. About 70% of the farmers planted sesame for both subsistence and commercial purposes. The majority of the farmers reported yields that ranged between 200 – 400 kg/ha which is still low as compared to yields realized in other regions. There is therefore need to train farmers in this region on the adoption of sesame improved agronomic practices and value addition. Moreover, there is need for all the stakeholders to develop proactive interventions aimed at improving sesame production for food security and increased earnings.